APPLICATION OF THE REVOLVING DIE IN HARDWARE PRODUCTION OF RUP “RECHITSKI HARDWARE PLANT” - V. I. Timoshpolski; M. L. German; N. V. Jakutovich; N. L. Mandel; V. G. Samonchik (Литьë и металлургия)
The results of analysis of the working of drawing equipment of RUP “Rechitsklj hardware plant” are given and the way of increase of its efficiency is indicated.